2020
DOI: 10.1371/journal.pone.0233054
|View full text |Cite
|
Sign up to set email alerts
|

Differential packaging of inflammatory cytokines/ chemokines and oxidative stress modulators in U937 and U1 macrophages-derived extracellular vesicles upon exposure to tobacco constituents

Abstract: Smoking, which is highly prevalent in HIV-infected populations, has been shown to exacerbate HIV replication, in part via the cytochrome P450 (CYP)-induced oxidative stress pathway. Recently, we have shown that extracellular vesicles (EVs), derived from tobacco-and/ or HIV-exposed macrophages, alter HIV replication in macrophages by cell-cell interactions. We hypothesize that cigarette smoke condensate (CSC) and/or HIV-exposed macrophagederived EVs carry relatively high levels of pro-oxidant and pro-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 52 publications
4
31
1
Order By: Relevance
“…Similar to the previous study, exposure to cigarette smoke condensate (CSC) increased the packaging of cytokines, especially IL-6 and CYPs (1A1 and 1B1) in EVs isolated from HIV-infected U1 macrophages [116]. Conversely, EV packaging of AOEs (SOD-1 and catalase) decreased in HIV-infected U1 macrophages more than in uninfected U937 macrophages [116]. Recently, our group showed that the astrocytic and neuronal-specific markers (GFAP and L1CAM) can be packaged in EVs and circulate in plasma, which is further elevated in the presence of HIV infection, alcohol, and/or tobacco [121].…”
Section: Hiv and Evssupporting
confidence: 78%
See 2 more Smart Citations
“…Similar to the previous study, exposure to cigarette smoke condensate (CSC) increased the packaging of cytokines, especially IL-6 and CYPs (1A1 and 1B1) in EVs isolated from HIV-infected U1 macrophages [116]. Conversely, EV packaging of AOEs (SOD-1 and catalase) decreased in HIV-infected U1 macrophages more than in uninfected U937 macrophages [116]. Recently, our group showed that the astrocytic and neuronal-specific markers (GFAP and L1CAM) can be packaged in EVs and circulate in plasma, which is further elevated in the presence of HIV infection, alcohol, and/or tobacco [121].…”
Section: Hiv and Evssupporting
confidence: 78%
“…However, exosomes derived from HIV-infected cells lost their protective capacity that could be due to the selective packaging of cytochrome P450 (CYPs) and antioxidant enzyme (AOE) mRNAs in exosomes [21]. Similar to the previous study, exposure to cigarette smoke condensate (CSC) increased the packaging of cytokines, especially IL-6 and CYPs (1A1 and 1B1) in EVs isolated from HIV-infected U1 macrophages [116]. Conversely, EV packaging of AOEs (SOD-1 and catalase) decreased in HIV-infected U1 macrophages more than in uninfected U937 macrophages [116].…”
Section: Hiv and Evssupporting
confidence: 64%
See 1 more Smart Citation
“…During infection, EVs can amplify inflammation and deflagrate antiviral responses (Urbanelli et al, 2019) and can also mediate communication between immune cells and other cell types (Isola and Chen, 2017). The involvement of EVs in viral infection and/or host interactions in disease has already been described for several viruses, such as rabies (Wang et al, 2019b), coronaviruses (Maeda et al, 1999;Kuate et al, 2007;Börger et al, 2020;Deffune et al, 2020;Hassanpour et al, 2020;Inal, 2020a;Inal, 2020b;Kumar et al, 2020;O'Driscoll, 2020;Tsuchiya et al, 2020;Urciuoli and Peruzzi, 2020), HCV (Bartosch et al, 2003;Timpe et al, 2008;Dreux et al, 2012;Bukong et al, 2014), HBV (Jia et al, 2017;, HIV (Princen et al, 2004;Khatua et al, 2009;Xu et al, 2009;Lenassi et al, 2010;Bernard et al, 2014;Raymond et al, 2016;Sampey et al, 2016;Kodidela et al, 2018;Haque et al, 2020;Ranjit et al, 2020), HPV (Honegger et al, 2015;Guenat et al, 2017;Sadri Nahand et al, 2019;Chiantore et al, 2020), HSV (Temme et al, 2010;Han et al, 2016;Deschamps and Kalamvoki, 2018) dengue (Martins et al, 2018;…”
Section: Evs In Immune Communication and Cytokine Responses During Inmentioning
confidence: 98%
“…U1 cells, which are U937 cells chronically infected with the human immunodeficiency virus type 1 (HIV-1), were procured from the NIH AIDS Reagent Program (Germantown, MD, USA). The U1 cell lines have been widely used by our group and many other research groups to study the role of drug abuse, including tobacco smoking in HIV replication [10,11,[22][23][24][25]. Furthermore, the results obtained using these cells have been successfully replicated in HIV-infected primary macrophages [10,11,24].…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%